Postgraduate Pediatric Training Programme in the Department of Child Health, Medical School University of Indonesia, Jakarta - H.E. Monintja; W.T. Karjomanggolo; R. Sutejo (Paediatrica Indonesiana, 1978)
Paediatrics is a major subject in undergraduate as well as postgraduate medical training. Demographic data show that 44% of the population in Indonesia as well as in other developing countries belongs to the paediatric age group. The objective of the training of paeditrician should be relevant to the needs of the society in child health care using the available potentials in the society and with the participation of the society. In this paper the determinant of objective, the objective, the methodology, the evaluation and the feedback system of the postgraduate paediatric training programme in the Department of Child Health, Medical School, University of Indonesia, is briefly described.